EVALUASI DAN PERENCANAAN SISTEM DRAINASE BERWAWASAN LINGKUNGAN DI JALAN H. MISTAR COKROKUSUMO KELURAHAN SUNGAI TIUNG CEMPAKA BANJARBARU - Alhaidar, Ihsan Nabil; Mazaya, Gusti Ihda; Abdi, Chairul; Khair, Riza Miftahul (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2024)
Because the capacity of natural or man-made channels can no longer support the flow of incoming rains, inundation may happen. Nearly every puddle in Cempaka District, with an average height of 20 cm and an inundation time of 6 hours or until the rain stops, is in a residential area, a rice field, or a plantation, according to the final report of the 2021 Banjarbaru City Environmental Road Drainage Masterplan. The goal of this plan is to study the anticipated flood flow, assess the drainage channel's capacity, suggest infiltration well proportions, and create a three-dimensional layout of the infiltration wells. With maximum daily rainfall data for 10 years (2012-2021), hydrological and hydraulic analysis was conducted for this design. According to the findings of the anticipated flood discharge calculation, segment 1 will experience a minimum discharge of 0.06 m3/s and a maximum discharge of 0.19 m3/s. This planning makes use of the Storm Water Management Model (SWMM) software, which enables modeling of the field's current drainage conditions by adding metrics collected under real circumstances. It is advised to include infiltration wells with a 1 m diameter and a 3 m well depth. To avoid flooding, infiltration wells will be installed to each section to lessen the projected flood flow that will enter the drainage canal and reach the water body.